Wayside school beneath the cloud of doom eaudiobook Wayside school series. - Sachar, Louis (Wayside School, 2020)
Wayside School is back in session in this brand-new, fourth installment in the perennially beloved and bestselling series by Newbery Medal-winning author Louis Sachar. Your favorite students and teachers are all here. That includes Sharie, who loves her striped-and-spotted umbrella more than anything; Kathy, who has a bad case of oppositosis; Jason, who has to read the longest book in the world; and the rest of Mrs. Jewls's class on the thirtieth floor, who are busily collecting toenail clippings. Everyone is scrambling to prepare for the all-important Ultimate Test, but meanwhile, there is a mysterious Cloud of Doom looming above them... More than fifteen million readers have laughed at the clever and hilarious stories of Wayside School. So what are you waiting for? Come visit Wayside School! Kids 7 to 13 will zoom through these chapter books—laughing their way through the fast, funny, silly but relatable stories. This funny chapter book series includes: Sideways Stories from Wayside School Wayside School Is Falling Down Wayside School Gets a Little Stranger And now also Wayside School Beneath the Cloud of Doom, the brand-new, fourth installment in the series, and the first in twenty-five years!